The Welfare State and Forced Sterilizations – The Swedish Case - Runcis, Maija (Romano džaniben, 2019)
The article presents a back drop on the state responsibility in Sweden for abuses and human rights violations made in the framework of Swedish sterilization policies during 1930s–1970s in relation to three groups of victims: the so called feebleminded and "unfit" individuals, socially vulnerable foster children in orphanages, and finally Swedish "travellers" (resandefolket) or the so-called "gypsies". The sterilization program is discussed in relation to Swedish welfare policies, its interconnection with eugenics, and gender and class bias in its implementation, focusing especially on the state focus on women. The Roma in Sweden represented an obviously a discriminated group, which however remain largely invisible in the sterilisation documents, since the sterilization policy during especially 1930s to 1950s, targeted "travellers", but not "Gypsies" as a special category. Exploring the mechanisms of the implementation of the sterilization legislations, the text touches upon the topics of power relations in the society, and ideas of race biology, gender and sexuality as treated in the social practices of the time. While compensation was offered to the first two groups of victims (which also include Roma), the relation of the Swedish state vis-a-vis the Roma as a specific category of victims of state abuse remains ambivalent.